Government Efforts to Protect Intellectual Property For Ki Masjong and Agus Cultural Heritage - Aditya Salsabila Consoleo; M.Sudirman; Benny Djaja (CV. ITTC INDONESIA, 2024)
The city of Serang in the Banten area has many social relics including the Banten area, the residence of Ki Masjong and Agus Ju. The lack of attention from the local government is one of the reasons and sources of problems that need to be solved, and there are still many cultural heritage sites in Serang City that have not been protected and managed properly. The process of examining information is carried out in a clear way, subjective, descriptive analysis aims to describe the results of observations from issues regarding the protection of the government against intellectual property, Cultural Heritage to IPR in Islam and general law, namely the Old Banten Pilgrimage based on Law Number 11 of 2010 concerning Cultural Heritage to then describe the obstacles faced by the City Education and Culture Office Therefore, it is hoped that the results of this study can present a complete picture of the central object of this research. This is the result of research and discussion that resulted in the conclusion that there is a lack of legal protection carried out by the Serang city government against the Old Banten Pilgrimage Cultural Heritage.